Popularization of Science in the Russian Mass Media: Challenges of Multimedia Formats - Bakanov, Roman P.; Egorova, Liliia; Mayorov, Victor; Tumanov, Dmitrii; Tyabina, Diana (Journal of History Culture and Art Research, 2018)
This article reveals the problems that are typical for the current state of popularization of scientific knowledge and scientific achievements in the Russian mass media. In terms of possible efficiency and effectiveness the authors analysed new formats currently used to cover the topic of science in the press at both the federal and regional levels. The content and comparative analyses of the five most popular Russian scientific journals and their websites (from the quality of articles to the structure of the websites of these journals, gaming, infographics, and the use of social networks in the practice of scientific popularization) enable us to conclude that journalists still have not explicitly taken full advantage of the new multimedia features provided by the Internet. In our opinion, this practice is not conducive to the “promotion” of the results of scientific research on mass audience. The authors of the article note the poor training of students of faculties and departments of journalism in the Russian universities concerning their acquired competencies related to their possible future professional activity in scientific or popular science journalism. The results of the research supplement the conclusions through the examples from the current practice of the Russian popularization of scientific knowledge to the results of research contained in current literature.